Brand Equity in Visual Inspection With Acetic Acid and Clinical Breast Examination: A Systematic Review - Achmad Fauzan Rachman; Stefanus Supriyanto; Wahdatul Chizbiyah; Monica Ayu Rossalya (Universitas Aisyah Pringsewu, 2023)
VIA and CBE examinations are services for the early detection of cervical cancer and breast cancer. The achievements of VIA and CBE examinations in Indonesia in 2019 are still very far from the target set, namely only 12.2% of the total number of women aged 30-50. This study aims to determine the relationship between brand equity, brand awareness, brand image, and brand trust on customer demand for VIA and CBE examinations. This research is a systematic review carried out according to the guidelines protocol of The Center for Review and Dissemination and the Joanna Briggs Institute Guideline and PRISMA checklist. The strategy for finding articles using the PICOS framework was carried out in September-October 2020. The data used included 10 national and international journal articles obtained through the database, namely Garuda, Scopus, Science Direct, Proquest, and SpringerLink. Articles search utilizing keywords and boolean operators (AND, OR, NOT, or AND NOT). The results show that of the 10 articles reviewed, 7 articles studied the VIA test method and 3 articles studied the CBE test method. The outcome in the form of the VIA and CBE test services utilization is influenced by brand equity which consists of brand awareness, brand image, and brand trust. The brand awareness and the brand trust of women towards the VIA and CBE tests are high as well as the brand image of the VIA and CBE tests that are good can increase customer demand for VIA and CBE examinations. It is hoped that health facilities will increase women's interest in utilizing VIA and CBE test services by promoting them effectively.